Analysis of the football coach verbal behavior in low categories regarding his federative formation and the moment of the match - David Sánchez Oliva; Pedro Antonio Sánchez Miguel; Diana Amado Alonso; Francisco Miguel Leo Marcos; Tomás García Calvo (FEADEF, 2010)
The aim of this study is to examine the differences regarding verbal instruction among football coaches from infantile and cadet category, taking into account as determinant variables their federative formation and the moment which is given that information. However, we analyzed four coaches, whom two of them had the federative license by the Extremeña Football Federation and two of them did not have it, and were measured their verbal conduct during a football match. After the registration of the data, we made the transcription of them with the purpose to establish the differences between groups. Through the data analyses, we showed significant differences with regard to the formation, whereas there were weak significant differences regarding the moment which the information was given. Finally, we emphasized the importance of the coach speech analysis in the scholar sport to optimize his work with respect to the instruction given to the players.